Final analysis of the prospective WSG-AGO EC-Doc versus FEC phase III trial in intermediate-risk (pN1) early breast cancer: efficacy and predictive value of Ki67 expression - Nitz, U.; Gluz, O.; Huober, J.; Kreipe, H. H.; Kates, R. E.; Hartmann, Arndt; Erber, Ramona; Scholz, M.; Lisboa, B.; Mohrmann, S.; Moebus, V.; Augustin, D.; et al. (Annals of Oncology, 2014)
Taxane-based adjuvant chemotherapy is standard in node-positive (N+) early breast cancer (BC). The magnitude of benefit in intermediate-risk N+ early BC is still unclear. WSG-AGO epiribicine and cyclophosphamide (EC)-Doc is a large trial evaluating modern taxane-based chemotherapy in patients with 1-3 positive lymph nodes (LNs) only.A total of 2011 BC patients (18-65 years, pN1) were entered into a randomized phase III trial comparing 4 × E90C600 q3w followed by 4 × docetaxel 100 q3w (n = 1008) with the current standard: 6 × F500E100C500 q3w (n = 828) or C600M40F600 d1, 8× q4w (n = 175). Primary end point was event-free survival (EFS); secondary end points were overall survival (OS), toxicity, translational research, and quality of life. Central tumor bank samples were evaluable in a representative collective (n = 772; 40%). Ki-67 was assessed centrally in hormone receptor-positive disease as a surrogate marker for the distinction of luminal A/B-like tumors.Baseline characteristics were well balanced between study arms in both main study and central tumor bank subset. At 59-month median follow-up, superior efficacy of EC-Doc [versus FEC (a combination of 5-fluorouracil, epirubicin, and cyclophosphamide)] was seen in EFS and OS: 5-year EFS: 89.8% versus 87.3% (P = 0.038); 5-year OS: 94.5% versus 92.8% (P = 0.034); both tests one-tailed. EC-Doc caused more toxicity. In hormone receptor-positive (HR)+ disease, only high-Ki-67 tumors (>= 20%) derived significant benefit from taxane-based therapy: hazard ratio = 0.39 (95% CI 0.18-0.82) for EC-Doc versus FEC (test for interaction; P = 0.01).EC-Doc significantly improved EFS and OS versus FEC in intermediate-risk BC (1-3 LNs) within all subgroups as defined by local pathology. In HR+ disease, patients with luminal A-like tumors may be potentially over-treated by taxane-based chemotherapy.ClinicalTrials.gov, NCT02115204.
EVALuna2:6696